Marine Materia Medica: Exploring the Therapeutic Potential of Sea Remedies through the Doctrine of Signatures. - Perween, Saba (Homoeopathic Heritage, 2026)
The marine realm remains an intriguing yet underexplored field in homoeopathic materia medica. Remedies derived from marine organisms and sea salts often mirror their environments. The Doctrine of Signatures proposes that a substance's form and habitat symbolically reflect its medicinal potential. For marine remedies, this links oceanic adaptations to symptom patterns observed in homoeopathic provings. This article critically reviews key sea remedies--Sepia, Spongia tosta, Natrum muriaticum, Medusa, Murex purpurea, Calcarea carbonica, Ambra grisea, and Corallium rubrum--highlighting their therapeutic value as interpreted through nature's signatures and clinical patterns. Integrating classical materia medica with modern views, it underscores the continued relevance of marine remedies in homoeopathy.